The Role of Lip Thickness in Upper Lip Response to Orthodontic Movement of Incisors - Alkadhi, Ruba. (2017)
Abstract: Aim: The aim of this retrospective study was to investigate the association between upper lip thickness and the amount of upper lip repositioning upon retraction of maxillary incisors. We also intended to explore the possible creation of a method for prediction of profile changes in orthodontic patients treated with premolar extractions based on their initial upper lip thickness. Hypothesis: Subjects with thick upper lips will experience less changes in upper lip position subsequent to retraction of maxillary incisors. Materials & Methods: Pre- and post-treatment lateral cephalograms of 101 patients (34 males and 67 females; mean age 14.8 years at pretreatment and 17.5 years at posttreatment) were evaluated. All patients were treated with fixed orthodontic appliances and extraction of two maxillary premolars or four premolars. Only subjects where lip thickness did not change more than 1 mm between pre- and post-treatment cephalograms were included. Hard and soft tissue landmarks were identified and digitized by one investigator (R.A.) using "View Box" software (Version 4.0.1.7., dHal software). Two constructed lines were established as reference lines: a vertical line that is perpendicular to sella-nasion line minus 7 degrees (SN-7º perpendicular), and another vertical line passing through subnasale (VL). Three linear measurements were identified in reference to those vertical lines: upper lip thickness, upper lip protrusion and maxillary incisor position. Results: The Pearson correlation coefficient revealed that there was a significant correlation between change in maxillary incisor position following premolars extraction and change in upper lip position (r = 0.95, p < 0.001) and (r = 0.88, p < 0.001) in reference to SN-7º perpendicular and VL, respectively. The average ratio between maxillary incisor retraction and upper lip repositioning was 1.4:1. However, the upper lip thickness was not significantly associated with this ratio (r = 0.003, p > 0.05) and (r = -0.155, p > 0.05) in reference to SN-7º perpendicular and VL, respectively. Conclusion: This study concluded that although there is a highly significant correlation between maxillary incisor retraction and upper lip repositioning, lip thickness does not have a significant association with the amount of upper lip repositioning. It appears that the amount of pretreatment compression of the upper lip due to maxillary incisor protrusion plays a primary role in profile change in patients where maxillary incisors are retracted.; Thesis (M.S.)--Tufts University, 2017.; Submitted to the Dept. of Orthodontics.; Advisor: Georgios Kanavakis.; Committee: Matthew Finkelman, and Carroll Trotman.; Keyword: Dentistry.